ANALYSIS OF THE EFFECT OF THE INTERACTIONS AMONG THREE PROCESSING VARIABLES FOR THE PRODUCTION OF EXOPOLYSACCHARIDES IN THE MICROALGAE Scenedesmus obliquus (UTEX 393) - CÓRDOBA-CASTRO, Nancy M.; MONTENEGRO-JARAMILLO, Andrés M.; PRIETO, Rosa E.; GONZÁLEZ-MARIÑO, Gloria E. (Vitae, 2012)
Microalgae are capable of producing biomolecules that have a wide variety of applications in agriculture, food industry, and medicine. In this study, three process variables are evaluated in order to determine its incidence on biomass and exopolysaccharides production. The effect of light intensity, agitation and carbon concentration on Scenedesmus obliquus (UTEX 393) growth and expolysaccaharides production is evaluated using 23 factorial design through the screening methodology. The simultaneous effect of level variation for three different experimental variables is examined in the present study in three levels for each parameter (Light intensity: 80, 130, 180 μE m-2 s-1, Agitation: 0, 600, 1200 rpm, carbon concentration 0, 2, 4% v/v Air-CO2). Specific growth rate and the exopolysaccharides concentration are the selected response variables. Results show that the optimal conditions for the two response variables correspond to the maximum levels of the three experimental variables (180 μE m-2 s-1, 4% air-CO2, and 1200 rpm), obtaining a specific growth rate of 0.64 d-1 and a exopolysaccharides concentration of 24.7 mg L-1. A significant interaction between the variables is observed, which has direct effects on cellular growth and exopolysaccharides production. The EPS production is facilitated by the turbulent flow (agitation maximum level), which is associated with a higher availability and better distribution of energy sources (light) and carbon dioxide. The validation of polynomials models verifies the relevance of the analysis performed.